Kenya food systems transformation book - Breisinger, Clemens; Keenan, Michael; Mbuthia, Juneweenex; Njuki, Jemimah (International Food Policy Research Institute, 2023)
The first years of the 2020s have brought a series of challenges to the Kenyan food system. COVID-19, locust infestations, droughts, the fallout of the Russia-Ukraine conflict, and global supply chain disruptions have strained agricultural production and tightened consumers’ budgets. These shocks are occurring against a backdrop of ongoing demographic shifts, urbanization, and stagnating agricultural production, and together demand a reexamination of our approach to food systems. Creating policy-relevant, empirical research for food systems transformation is more important than ever, as policy aims to address current challenges to promote food production, resilience, sustainability, nutrition, and gender equality. Food Systems Transformation in Kenya: Lessons from the Past and Policy Options for the Future presents empirical research from across the various components of the Kenyan food system and is an ambitious undertaking designed to paint a holistic view of where Kenya’s food system has been and where it can go. Considering the diversity of challenges and opportunities within the Kenyan food system, this volume approaches a multitude of problems facing the food system using a variety of empirical methods to give insights on evidence-based policy pathways. The contributors for this book demonstrate the spirit of collaboration for solving the 21st century’s toughest problems—academics from Kenyan universities, researchers from Kenyan research institutes, International Food Policy Research Institute (IFPRI) colleagues, other CGIAR researchers, international academics, and experts from multilateral institutions came together to make this far-reaching book a reality. Through this unique combination of national and international expertise, Food Systems Transformation in Kenya provides comprehensive and useful information for decisionmakers in Kenya. It will also spark discussions on food systems transformation among students, researchers, and policymakers to strengthen the science-policy dialogue while also serving as source of learning and inspiration for other countries. We look forward to the Ministry of Agriculture and Livestock Development’s continued collaboration with IFPRI, CGIAR, and other partners in creating research-based policy recommendations that will lead to a brighter, healthier future for all Kenyans.